Encyclopedia of Magnetic Resonance 2008
DOI: 10.1002/9780470034590.emrstm1007
|View full text |Cite
|
Sign up to set email alerts
|

Crystallography and NMR: An Overview

Abstract: Advances in technology are rendering some of these difficulties less restrictive. In addition, in recent years, the power of powder diffraction techniques has been greatly increased so that it is feasible in many cases to obtain detailed crystal structures by this means. 9 This is particularly valuable, for example, for samples of small crystals embedded in an amorphous matrix, as is the case for many ceramic systems. Other advances in X-ray diffraction procedures allow electron

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…This can be explained by the pronounced crystalline nature of the sample. At the same time, the spectra of the cis isomer did not depend on the physical outlook of the sample; they always showed amorphous character 11…”
Section: Resultsmentioning
confidence: 92%
“…This can be explained by the pronounced crystalline nature of the sample. At the same time, the spectra of the cis isomer did not depend on the physical outlook of the sample; they always showed amorphous character 11…”
Section: Resultsmentioning
confidence: 92%
“…[7][8][9][10][11][12][13][14][15][16][17] There is an increasing interest in "NMR crystallography", which pertains to obtaining molecular-level and crystal structure information for solid materials using SSNMR data. 18 Although there have been a number of exciting recent advances in this area of research, 6,[19][20][21][22][23][24][25] one cannot currently convert SSNMR data into a unique solid-state structure in a completely generalized manner. With a small amount of a priori knowledge, however, NMR crystallography methods have been applied to solve and refine the structures related to certain classes of materials, such as zeolites, [26][27][28] which are sometimes subject to crystal twinning and typically do not possess enough long-range order to produce crystals that would be considered suitable for X-ray diffraction (XRD) studies.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the isotropic chemical shift spectrum cannot resolve the 8 molecules in the unit cell, a degeneracy of chemical shifts well known in NMR crystallography . [3][4][5] The CODEX pulse sequence is based on magnetization exchange among nearby spins and is more sensitive than multiple quantum [6][7][8][9] approaches to determine oligomeric number or inequivalent molecules in crystals. The sequence was first invented by Schmidt-Rohr et al for investigation of slow dynamics [10,11] and later demonstrated by Hong et al for the application of determining oligomeric numbers and intermolecular distances.…”
mentioning
confidence: 99%